Pengaruh Tingkat Pendidikan, Usia, Dan Peringkat Penggajian (Grading) Terhadap Kinerja Pegawai Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Kalimantan Barat - Muhammad Nur (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aimed to determine the effect of education level, age, rank and payroll (grading) on employee performance DJPB Regional Office of West Kalimantan Province. The method used is descriptive method, while data collection technique consists of observation, interviews, and questionnaires. Object of this research is all that exists in the Regional Office DJPB West Kalimantan which amounts to 67 employees. The analysis used was the Anova test and Independent Sample T Test. The results of this study showed that the mean performance is 104.31. For the ANOVA test of the level of education shows that F count larger than F table (4.313> 3.140) which means that H0 is rejected and it can be concluded that the average performance for the level of education is not the same or there is a difference. As for the differences found in employee education level education level S2 S2 which differ significantly with education level below the S1 and S1. For the ANOVA test for age showed that the F table Bigger than F count (3.140> 0.658) which means that H0 is accepted and it can be concluded that the average performance for the same level or age is no difference. To test for independent samples t grade indicates that the arithmetic ≤ t table ≤ t, ie -2.281 <1.997 <2.281, which means that H0 is accepted and it can be concluded that there is no difference between the average performance level of high grade and low grade.